2010
DOI: 10.1210/en.2009-1368
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of (Pro)Renin Receptor Expression by Glucose-Induced Mitogen-Activated Protein Kinase, Nuclear Factor-κB, and Activator Protein-1 Signaling Pathways

Abstract: Renal (pro)renin receptor (PRR) expression is increased in diabetes. The exact mechanisms involved in this process are not well established. We hypothesized that high glucose up-regulates PRR through protein kinase C (PKC)-Raf-ERK and PKC-c-Jun N-terminal kinase (JNK)-c-Jun signaling pathways. Rat mesangial cells exposed to 30 mm d-glucose demonstrated significant increase in PRR mRNA and protein expression, intracellular phosphorylation of Raf-1 (Y340/341), ERK, JNK, nuclear factor-kappaB (NF-kappaB) p65 (S53… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 40 publications
2
50
0
Order By: Relevance
“…ERK1/2 and NF-κB in response to glucose and Ang II Huang et al showed that glucose increased the phosphorylation of ERK1/2, JNK and NF-κB-p65 in rat mesangial cells [13] . Glucose (25 mmol/L) has also been shown to stimulate the phosphorylation of ERK1/2 in cardiac fibroblasts [12] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ERK1/2 and NF-κB in response to glucose and Ang II Huang et al showed that glucose increased the phosphorylation of ERK1/2, JNK and NF-κB-p65 in rat mesangial cells [13] . Glucose (25 mmol/L) has also been shown to stimulate the phosphorylation of ERK1/2 in cardiac fibroblasts [12] .…”
Section: Resultsmentioning
confidence: 99%
“…Ang II and glucose-induced collagen accumulation in the cultured cardiac fibroblasts has also been demonstrated to involve the activation of ERK1/2 and NF-κB [10,12,32] . High concentrations of glucose and Ang II can indeed activate ERK1/2 and/or NF-κB in other types of cells [13] . These previous data were confirmed in the present study in mouse cardiac fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…First, blocking the AT1 receptor reduces the oxidative stress and NF-κB stimulation induced by high glucose because both of these effects are known to increase (P)RR expression. 24,25 Second, it has previously been demonstrated that renin suppresses (P)RR expression through the PLZF pathway. 20 Because RAS inhibitors cause a rise in renin and prorenin levels, it is possible that the increased production of renin during the AT1 receptor blockade downregulates (P)RR expression.…”
Section: Discussionmentioning
confidence: 99%
“…Increases in (P)Rr expression occur in diabetes and as a response to high glucose [78], and have also been linked to hypertension and increased heart-rate in rats [79].…”
Section: Discussionmentioning
confidence: 99%